Methyl-branched lipids promote the membrane adsorption of α-synuclein by enhancing shallow lipid-packing defects. Issue 24 (28th June 2015) - Garten, Matthias; Prévost, Coline; Cadart, Clotilde; Gautier, Romain; Bousset, Luc; Melki, Ronald; Bassereau, Patricia; Vanni, Stefano
<x xml:space="preserve">Abstract</x> Reconstitution experiments on Giant Unilamellar Vesicles and Molecular Dynamics Simulations indicate that alpha-synuclein binds to neutral flat membranes in the presence of methyl-branched lipids.